Changes in US Monetary Policy and Its Transmission over the Last Century. Issue 4 (1st November 2017) - Breitfuß, Sebastian; Feldkircher, Martin; Huber, Florian
Abstract: In this paper, we investigate US monetary policy and its time‐varying effects over more than 130 years. For that purpose, we use a Bayesian time‐varying parameter vector autoregression that features modern shrinkage priors and stochastic volatility. Our results can be summarized as follows: First, we find that monetary policy transmits jointly through the interest rate, credit/bank lending and wealth channels. Second, we find evidence for changes of both responses to a monetary policy shock and volatility characterizing the macroeconomic environment. Effects on the macroeconomy are significantly lower in the period from 1960 to 2013 than in the early part of our sample, whereas responses of short‐ and long‐term interest rates are nearly unaltered throughout the sample. Changes in the way the Fed conducts monetary policy and different economic environments may account for that.